Research on the Application of Reverse PoE - Zhanhai Zhuang; Jiankang Chen (Dianxin kexue)
Based on the power supply demands of broadband access network，the equipments，wiring surrounding，multi-users balanced power supply and administration，security/protection about the reverse PoE application were studied and a test was done in laboratory.All those can provide reliable theory and experience for the reverse PoE construction and promote the development of the application of reverse PoE.